2013
DOI: 10.1016/j.ijdevneu.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for carbamoyl phosphate synthetase 2 in cranial sensory circuit formation

Abstract: In zebrafish, cranial sensory circuits form by 4 days post-fertilization. We used a forward genetic screen to identify genes involved in the formation of these circuits. In one mutant allele, sl23, axons arising from the epibranchial sensory ganglia do not form their stereotypical terminal fields in the hindbrain. These embryos also had small eyes and deformed jaws, suggesting a pleiotropic effect. Using positional cloning, a 20-nucleotide deletion in the carbamoyl-phosphate-synthetase2-aspartate-transcarbamyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Despite being alive and apparently healthy and fertile, this animal had very poor udder morphology (scored among the lowest 1% of animals with same sire; Figure 1). This is consistent with previous observations in model organisms and humans, in which deleterious mutations in CAD lead to embryonic lethality with incomplete penetrance (Norby, 1973;Falk and Nash, 1974;Willer et al, 2005;Franks et al, 2006;Cox et al, 2014;Ng et al, 2015). Of note, studies in humans and Drosophila demonstrated that uridine supplementation reduces the severity of the symptoms by the salvage pathway of pyrimidine biosynthesis (Falk and Nash, 1974;Ng et al, 2015;Koch et al, 2017).…”
Section: Surviving Cad Homozygotes Exhibit Broad Range Of Symptoms Desupporting
confidence: 91%
“…Despite being alive and apparently healthy and fertile, this animal had very poor udder morphology (scored among the lowest 1% of animals with same sire; Figure 1). This is consistent with previous observations in model organisms and humans, in which deleterious mutations in CAD lead to embryonic lethality with incomplete penetrance (Norby, 1973;Falk and Nash, 1974;Willer et al, 2005;Franks et al, 2006;Cox et al, 2014;Ng et al, 2015). Of note, studies in humans and Drosophila demonstrated that uridine supplementation reduces the severity of the symptoms by the salvage pathway of pyrimidine biosynthesis (Falk and Nash, 1974;Ng et al, 2015;Koch et al, 2017).…”
Section: Surviving Cad Homozygotes Exhibit Broad Range Of Symptoms Desupporting
confidence: 91%
“…Standard mapping methods using bulk segregant and meiotic recombination analysis of microsatellite markers (Green et al, 2009 ; Cox et al, 2014 ) were used to map the sl19 mutation to a critical interval on chromosome 14. Total RNA was then extracted from mutant and wild type 4 days post fertilization (dpf) larvae and cDNA synthesized with Superscript III reverse transcriptase (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…RNA (100 pg/nl) or morpholino oligonucleotides (MO; Gene Tools, 1–2 ng/nl, Supplementary Table S2 ) were injected as previously described (Cox et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations